Analysis of the Effectiveness of Quality Management through the Implementation of Quality Assurance (QA) and Quality Control (QC) in Improving Microbiology Laboratory Examination Results at Grandmed Hospital Lubuk Pakam - Rahmawati; Ahmad Hafizullah Ritonga; Sa’adah Siregar (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Microbiology laboratories play an important role in supporting diagnosis and clinical decision-making, so the quality of test results must be guaranteed. The complexity of the testing process requires the consistent application of quality management through Quality Assurance (QA) and Quality Control (QC) at all stages of pre-analytical, analytical, and post-analytical. This study aims to analyze the effectiveness of QA and QC implementation in improving microbiology laboratory test results at Grandmed Lubuk Pakam Hospital. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and quality document reviews of the head of the laboratory, the doctor in charge, microbiology laboratory analysts, and administrative staff. Data analysis was conducted thematically to examine the QA and QC implementation process and factors affecting the effectiveness of quality management. The results showed that QA and QC had been implemented through SOPs, internal quality control, result validation, and quality documentation. However, their implementation has not been optimal due to limited human resources, overlapping tasks, and inconsistent evaluation and follow-up of quality audits. Nevertheless, the implementation of QA and QC has contributed positively to improving the reliability of test results and clinician confidence. The conclusion of this study is that the effectiveness of microbiology laboratory quality management through the implementation of QA and QC is influenced by the adequacy of human resources, management commitment, and consistency of implementation at the operational level